METAPHORS IN JAVANESE MANTRA OF KIYAI PRADAH RITUAL CEREMONY - Imroatus Solikhah (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2016)
The objective of this study is to see the meaning of metaphors in traditional ceremony in Lodoyo named Kiyai Pradah. This study  was ethnography that used qualitative approach. The focus of this study was metaphors identified from the Javanese mantras used for ritual ceremony of Kiyai Pradah in Lodoyo, Blitar. The metaphors were analyzed their literal symbols and their intended meaning based on the Javanese culture. Data were analyzed using category of methapors and interpreting the symbols into the intended meaning.  This study concludes that metaphors used in Javanese mantras of Kiyai Pradah ritual consist of 20 kinds. The metaphors are categories into (1) complimentary metaphors, (2) predicative metaphors, and (3) sentential metaphors. The metaphors represent the Javanese teaching values that put respects and harmony among human beings, the ancestors, and God.